E-GOVERNANCE DAN PEMBERDAYAAN MASYARAKAT - Muhammad Herowandi (Majalah Ilmiah Dinamika Administrasi (MIDA), 2022)
In this disruption era, internet of things and digitalization are things that are inseparable from today’s everyday life. It happens in all aspects of our society, including the public administration services. Thus, it coined the term “e-governance” to depict how digitalization has affected the government in enhancing their performance Olehby digitalizing their public services. This is a research to discover how the digitalization of the public service could affect society’s empowerment. The method used in this research was library research where literatures that are relevant to the research topic were collected and analyzed. The research implied that the application of e-governance had an important role in empowering the society as the public services become more accessible than before. However, the human resource, especially those in the rural areas needs to be improved in order to maximize the expected process and outcome from the digitalized public services. Keywords; E-governance; Public services; Digitalization; Internet; Society empowerment